Mechanosensing in Myosin Filament Solves a 60 Years Old Conflict in Skeletal Muscle Modeling between High Power Output and Slow Rise in Tension - Marcucci, Lorenzo; Reggiani, Carlo (Frontiers in Physiology, 2016)
Almost 60 years ago Andrew Huxley with his seminal paper [Huxley1957] laid the foundation of modern muscle modeling, linking chemical events to mechanical performance. He described mechanics and energetics of muscle contraction through the cyclical attachment and detachment of myosin motors to the actin filament with ad hoc assumptions on the dependence of the rate constants on the strain of the myosin motors. That relatively simple hypothesis is still present in recent models, even though with several modifications to adapt the model to the different experimental constraints which became subsequently available. However, already in that paper, one controversial aspect of the model became clear. Relatively high attachment and detachment rates of myosin to the actin filament were needed to simulate the high power output at intermediate velocity of contraction. However, these rates were incompatible with the relatively slow rise in tension after activation, despite the rise should be generated by the same rate functions. This discrepancy has not been fully solved till today, despite several hypotheses have been forwarded to reconcile the two aspects. Here, using a conventional muscle model, we show that the recently revealed mechanosensing mechanism of recruitment of myosin motors [Linarietal2015] can solve this long standing problem without any further ad-hoc hypotheses.